Accessible Virtual Arts Recreation for Wellbeing Promotion in Long-Term Care Residents. (May 2021) - Murphy, Kelly J.; Swaminathan, Swathi; Howard, Elizabeth; Altschuler, Aviva; Rogan, Jessica; Beauchet, Olivier; Dupuis, Kate; Galea, Liisa A. M.; Hogan, David; Lingum, Navena; Rowe, Gillian; Tsotsos, Lia; et al.
The efficacy of a technology-driven visual arts recreation activity, delivered virtually, was evaluated for its potential to achieve positive impacts, similar to traditional arts-interventions, on wellbeing in long-term care residents. Thirty-one residents (average age 86.8 years; SD = 9.4) engaged with the arts-intervention for 30-minutes, twice weekly, for 6 weeks with either a partner or as part of a group. Wellbeing indicators included self-reported psychological and health-related wellness, and attention capacity. Binomial tests of postintervention change revealed a significant above-chance probability of improvement in one or more wellbeing indicators ( p < .05). Postparticipation feedback survey scores were positive ( p < .05). Cognitive status did not influence outcome; however, other participant characteristics such as younger age, higher openness-to-experience (personality trait), and lower baseline mood were significantly associated with positive response to the intervention ( p < .05). Findings demonstrate technology may be an effective platform for promoting accessibility to beneficial arts-interventions for older adults.